Analysis and Estimation of Harmonics using Wavelet Technique - V Thiyagarajan; N.P. Subramanium (Institute of Advanced Engineering and Science, 2015)
The paper develops an approach based on wavelet technique for the evaluation and estimation of harmonic contents of power system waveform. The proposed algorithm decomposes the signal waveforms into the uniform frequency sub-bands corresponding to the odd harmonic components of the signal. The proposed implementation of algorithm determines the frequency bands of harmonics which retain both the time and frequency relationship of the original waveforms and uses a method to suppress those harmonics. The wavelet algorithm is selected to obtain compatible output bands with the harmonic groups defined in the standards for power-supply systems. A comparative analysis will be done with the input and the results obtained from the wavelet transform (WT) for different measuring conditions and Simulation results are given. DOI: http://dx.doi.org/10.11591/telkomnika.v13i2.6983